Development of bio-based thermoplastic polyurethanes formulations using corn-derived chain extender for reactive rotational molding - K. Prashantha; B. J. Rashmi; D. Rusu; M-F. Lacrampe; P. Krawczak (eXPRESS Polymer Letters)
Partly bio-based segmented thermoplastic polyurethane (TPU) formulations were developed to fulfill the requirements of the reactive rotational molding process. They were obtained by one-shot bulk polymerization between an aliphatic diisocyanate (1,6-hexamethylene diisocyanate), a polyether polyol as macrodiol (polyethylene glycol) and a biobased corn-derived 1,3-propanediol as chain extender (CE), in presence of a catalyst, at an initial temperature of 45°C. Equivalent TPU formulations with classical petroleum-based 1,3-propanediol were also prepared for a purpose of comparison. TPU with different soft to hard segment (SS/HS) ratios were synthesized by varying the macrodiol and CE concentrations in the formulations. For each formulation, the evolution of the reaction temperature as a function of time was monitored and the kinetics of polymerization was studied by Fourier Transform infrared spectroscopy in attenuated total reflection mode (FTIR-ATR). The morphology, thermal properties, solubility in different solvents and tensile properties of the final products were analyzed. All synthesized polyurethanes are 100% linear polymers and the extent of microphase separation, as well as the thermal and mechanical properties highly depends on the HS content, and glass transition temperature and Young modulus can be tuned by adjustment of the SS/HS ratio. All results indicate that petrochemical CE can be replaced by its recently available corn-derived homologue, without sacrificing any use properties of the final polyurethanes.